Atlas: Understanding What Makes Systems Engineers Effective in the U.S. Defense Community. Issue 6 (November 2016) - Hutchison, Nicole; Henry, Devanandham; Pyster, Art
ABSTRACT: Atlas is a theory of what makes systems engineers effective. The primary data to date on which Atlas is based comes from the U.S. defense community, but indications are that the theory is applicable to other business sectors as well. Based primarily on qualitative analysis of interviews with 287 individuals from 20 organizations in the DoD, defense industrial base, and commercial industry, Atlas identifies the key characteristics of systems engineers, explains what promotes and inhibits their effectiveness, and identifies how organizations are attempting to improve effectiveness of their systems engineering workforce. In Atlas, a systems engineer is considered effective when she consistently delivers value. This fundamental definition of effectiveness hinges on "value." Although each organization defines what it most values in its systems engineers, the most commonly‐cited values include: keeping and maintaining the system vision, enabling diverse teams to successfully develop systems, managing emergence in both the project and the system, enabling good technical decisions at the system level, supporting the business cases for systems, and translating technical jargon into business or operational terms and vice versa. In order to provide these values, system engineers must have the right proficiencies—knowledge, skills, abilities, behaviors, and cognition—and the right personal and organizational characteristics to support their work. This paper describes both Atlas and the insight it offers into what makes systems engineers effective.